Sex‐Based Differences in the Biodistribution of Nanoparticles and Their Effect on Hormonal, Immune, and Metabolic Function - Maria Poley; Gal Chen; Noga Sharf-Pauker; Aviram Avital; Maya Kaduri; Mor Sela; Patricia Mora Raimundo; Lilach Koren; Sivan Arber; Egor Egorov; Janna Shainsky; Jeny Shklover; et al. (Advanced NanoBiomed Research, 2022)
Males and females respond differently to medications due to physiologic, metabolic, and genetic factors. At times, sex‐related differences cannot be mitigated by dose adjustment to body mass, and are evident from the tissue level to the single cell. The rising number of clinically approved nanotechnologies calls for assessing how their activity is affected by the patient's sex. Herein, sex differences in nanotechnology are scoped, with emphasis on molecular considerations. Sex‐specific pharmacokinetics of nanocarriers is influenced by the nanoparticle's composition, its size, and architecture. The biodistribution and immune response to nanoparticles in males and females, and the influence nanoparticles have on hormones, fertility, and toxicity, are discussed. Despite its importance, the effect of sex on the design and implementation of nanomedicines is underresearched. Herein, it is aimed to raise awareness of sex differences in the preclinical and clinical evaluation of nanotechnologies.